Viktor Astafyev’s Literary Discourse (Based on His Correspondence) - Borkowska, Aldona (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2014)
The aim of the article is to survey the correspondence of Viktor Astafyev, published in three different books, for statements about the work of contemporary writers, his own creativeness and comments on literary life in the Soviet Union and Russia. It is worth noting that the Siberian prose writer exchanged letters with critics and writers for many years. In the text much attention is paid to his critical opinions and evolving views on the Russian literature.